Associations between classroom normative climate and the perpetration of teen dating violence among secondary school students - Beckmann, Laura (Journal of interpersonal violence, 2019)
The aim of this study was to investigate how classroom normative climate regarding the perpetration of teen dating violence (TDV) was related to adolescents’ self-reported perpetration of (verbal/emotional, threatening, relational, physical, and sexual) violence within romantic relationships in the previous 12 months. Based on Theory of Normative Conduct, we hypothesized that higher classroom levels of TDV perpetration were associated with a higher likelihood of individual TDV perpetration. Data were drawn from a large survey of ninth-grade students conducted in the state of Lower Saxony, Germany (n = 10,638). From this sample, an analysis sample of n = 4,351 students at risk was drawn (mean age: 15.0, SD: 0.76; 46.6% male). More than half (54.8%) of the at-risk sample reported engagement in any form of TDV within the previous 12 months, whereby rates varied considerably by the dimension of TDV. Controlling for a range of risk factors on the classroom level (proportion of students dependent on social welfare, proportion of students with migration background) and individual level (exposure to family violence, sociodemographic characteristics, TDV victimization, and peer- and school-related factors), regression analyses showed that higher rates of classroom-level TDV perpetration were positively related to individual verbal/emotional TDV perpetration. This pattern of results was observable across all dimensions of TDV. Furthermore, gender-specific patterns of TDV perpetration were observable: Girls were more affected by classroom levels of verbal/emotional and physical TDV than boys, while boys were more affected by classroom levels of relational and sexual TDV. Results highlight the role of the wider peer context in shaping adolescent dating experiences and specifically point to the relevance of the classroom ecology for the socialization of dating violence in adolescents.